Urinary NGAL is a Potential Biomarker for Early Renal Injury in Insulin Resistant Obese Non-diabetic Children - Semra Şen (Galenos Yayincilik, 2021)
Objective:Neutrophil gelatinase-associated lipocalin (NGAL) is one of the new biomarkers for detecting acute renal injury. There are studies showing the relationship between NGAL and renal injury in obese children. The aim of this study was to investigate whether urinary levels of NGAL, kidney injury molecule-1, and serum cystatin C are increased in insulin resistance (IR) patients before the development of diabetes.Methods:Cross-sectional, case-controlled study that included non-diabetic obese children and adolescent patients with IR and a nondiabetic obese control group with no IR, who attended a tertiary center pediatric endocrinology outpatient clinic between 2016-2018. Those with diabetes mellitus and/or known renal disease were excluded. NGAL and creatinine (Cr) levels were evaluated in the morning spot urine from all participants. Serum renal function was evaluated.Results:Thirty-six control and 63 IR patients were included in the study, of whom 68 (68.7%) were girls. The mean age of all participants was 13.12±2.64 years and no statistically significant difference was found between the two groups in terms of age or gender distribution. Median (range) spot urinary NGAL (u-NGAL) values in the IR group were significantly higher at 26.35 (7.01-108.7) ng/mL than in the control group at 19.5 (3.45-88.14) ng/mL (p=0.018). NGAL/Cr ratio was also significantly higher in the IR group compared to the control group (p=0.018).Conclusion:Obese pediatric patients with IR were shown to have elevated levels of u-NGAL, a marker of renal injury. u-NGAL examination may show early renal injury before development of diabetes.